Development of an online secondary prevention programme for stroke survivors: Prevent 2nd Stroke. Issue 1 (14th March 2019) - Denham, Alexandra M J; Guillaumier, Ashleigh; McCrabb, Sam; Turner, Alyna; Baker, Amanda L; Spratt, Neil J; Pollack, Michael; Magin, Parker; Oldmeadow, Christopher; Collins, Clare; Callister, Robin; Wallis, Mark; et al.
Abstract : Background: Stroke events often result in long-term negative health outcomes. People who experience a first stroke event are 30%–40% more likely to experience a second stroke event within 5 years. An online secondary prevention programme for stroke survivors may help stroke survivors improve their health risk behaviours and lower their risk of a second stroke. Objectives: This paper describes the development and early iteration testing of the usability and acceptability of an online secondary prevention programme for stroke survivors (Prevent 2nd Stroke, P2S). P2S aims to address six modifiable health risk behaviours of stroke: blood pressure, physical activity, nutrition, depression and anxiety, smoking, and alcohol consumption. Methods: P2S was developed as an eight-module online secondary prevention programme for stroke survivors. Modelled on the DoTTI (Design and development, Testing early iterations, Testing for effectiveness, Integration and implementation) framework for the development of online programmes, the following stages were followed during programme development: (1) content development and design; and (2) testing early iteration. The programme was pilot-tested with 15 stroke survivors who assessed P2S on usability and acceptability. Results: In stage 1, experts provided input for the content development of P2S. In stage 2, 15 stroke survivors were recruited for usability testing of P2S. They reported high ratings of usability and acceptability of P2S. P2S was generally regarded as 'easy to use' and 'relevant to stroke survivors'. Participants also largely agreed that it was appropriate to offer lifestyle advice to stroke survivors through the internet. Conclusions: The study found that an online secondary prevention programme was acceptable and easily usable by stroke survivors. The next step is to conduct a randomised controlled trial to assess the effectiveness of the programme regarding behaviour change and determine the cost-effectiveness of the intervention.